Transcription-Based Multidimensional Regulation of Fatty Acid Metabolism by HIF1α in Renal Tubules - Li, Wenju; Duan, Aiping; Xing, Yuexian; Xu, Li; Yang, Jingping (Frontiers in Cell and Developmental Biology, 2021)
Lipid metabolism plays basic role in renal physiology, especially in tubules. Hypoxia and Hypoxia induced factor (HIF) activation are common in renal diseases, however, the relationship between HIF and tubular lipid metabolism are poorly understood. Using prolyl hydroxylase inhibitor roxadustat (FG-4592), we verified and further explored the relationship between sustained HIF1α activation and lipid accumulation in cultured tubular cells. Transcriptome and chromatin immunoprecipitation sequencing analysis revealed that HIF1α directly regulate the expression of a number of genes possibly affecting lipid metabolism, including those associate with mitochondrial function. HIF1α activation suppressed fatty acid (FA) mobilization from lipid droplet and extracellular FA uptake. Moreover, HIF1α decreased FA oxidation and ATP production. Lipidomics analysis showed that prolyl hydroxylase inhibitor caused strong triglycerides accumulation, and increased several proinflammatory lipids, while maintaining the overall FA level. Thus, our study indicated that HIF1α reduced FA supply and utilization and reconstructed composition of lipids in tubules, which could be a part of hypoxic adaption but could also be involved in the pathological processes in kidney.